Vocabulary Learning and Teaching through Student Teacher Negotiations in the Malaysian ESL Classroom - Mohd Rasdi, Roslina (2009)
This study was conducted with the aim of investigating how vocabulary was taught and learned in three selected Malaysian schools. Specifically, it sought to explore the extent to which negotiation between students and teachers occurs in vocabulary learning and teaching. The study is delineated into by three research questions that are concerned with the strategies used by the upper secondary teachers and students in vocabulary learning and teaching respectively; the perception of upper secondary teachers’ and students’ on the use and importance of student-teacher negotiation in learning and teaching vocabulary; and how negotiation between upper secondary students and teachers takes place in vocabulary learning and teaching in the Malaysian second language classroom. A basic or generic qualitative research methodology was employed to answer these three research questions. For the purpose of triangulation, data was collected through classroom observations, one-to-one semi-structured interview with the teachers, and focus group discussion (FGD) with the students. Specifically, six classroom observations were conducted to elicit the natural negotiation process between students and teachers during vocabulary learning and teaching. The English teachers from the observed classes were then interviewed to corroborate the findings of the classroom observations. Lastly, students from each observed class were selected to participate in the focused-group discussion. All collected data were either video or audio-taped, transcribed verbatim and triangulated. Reliability and validity were further ascertained through member checks, peer examination and maintenance of audit trail. The findings showed that incidental vocabulary learning and teaching (VLT) was the primary approach used by students and teachers in learning and teaching vocabulary. The classroom observations revealed that six strategies were employed in incidental VLT, one of which is student-teacher negotiation. The semi-structured interview and FGD showed that, generally, teachers and students have positive and negative perceptions towards student-teacher negotiation in VLT. The findings also showed that negotiation between upper secondary students and teachers took place under four conditions: creating an enjoyable and safe learning environment, preparing activities which were able to gain or capture the students’ interest to communicate, integrating negotiation with other vocabulary learning strategies, and placing the students with the same level of English in one class. An additional finding of the study was factors that promote or inhibit negotiation in the classroom. A conclusion of the study is that student-teacher negotiation seemed to be beneficial, but is not fully implemented by teachers and students. Theoretical and pedagogical implications are noted, and recommendations for further research are also suggested.